UKRAINE VECTORS IN THE DEVELOPMENT OF THE EUROPEAN UNIVERSITY EDUCATION (Educological discourse, 2014)
This article outlines some areas of university education, in particular the formation of the new type of thinking – innovation in the context of the new global paradigm of thinking of the XXI century. The types of innovative thinking that shape a new generation of people are outlines. Author determined trends in the development of university education in the context of which is the formation of an innovative mindset. Pay attention on the focus on the principles and priorities of modernization of university education in the context of the formation of the innovative thinking in the information society.